Formation and stability of oil‐laden foam: Effect of surfactant and hydrocarbon solvent. (16th June 2021) - Lin, Feng; Ng, Jason K.; Huang, Yueying; Huang, Charley; Zeng, Hongbo
Abstract: Oil‐laden (OL) foams could serve an important role in various processes, particularly in enhanced oil recovery; however, OL foams are less studied than aqueous foams. In this work, the formation and stability of OL foam, by either sodium dodecyl sulphate (SDS) or Triton X‐100 (TX‐100) in water‐pentane mixture, was evaluated. We first constructed a diagram of good and poor foaminess against pentane content in the mixture and aqueous surfactant concentration. It was shown that surfactant onset concentration for good foaming was increased with increasing pentane content. The result was fitted using a mathematical model that considers the surfactant dilution and adsorption effects by pentane. Foam height decay profiles were also monitored. Results indicated that SDS resulted in a more stable foam than TX‐100 at the same critical micelle concentration (CMC). Depending on surfactant concentration, OL foams exhibited strikingly different stability behaviours. Pentane acted as an anti‐foamer at surfactant concentrations at the CMC or lower. However, very high foam stability was displayed at high surfactant concentration (e.g., 3× CMC) and medium to high pentane contents; this is a result contradictory to the predication of entering, spreading, and bridging coefficients in the classic theory. The stable OL foams of this study could be attractive to potential foam applications.